Musykilāt Tanfīż at-Ṭarīqah at-Tamṡīliyyah fī Ta’līm al-Muḥādaṡah fī MTs Al-Falāh Sumber Gayam Kadur Pamekasan - Cicik Aini; Asni Furoidah (Al-Fusha : Arabic Language Education Journal, 2021)
Teachers need to have innovations in teaching Arabic conversation through the right method in order to obtain maximum results. This article aimed to describe the application of the role playing method in Arabic conversation at MTs Gayam Kadur Pamekasan. Researchers used a qualitative approach with descriptive analysis. Some of the obstacles in learning conversation with role playing were that the teacher did not understand it well, differences in student abilities, lack of teaching materials, and it takes a lot of time and a large space. The application of role playing has a high level of effectiveness if it is supported by the ability of teachers and student motivation in addition to a pleasant learning atmosphere.